Factors Affecting Antenatal Care Examination on Pregnant Women in the Work Area of Hinai Kiri Health Center, Langkat Regency - Mardiuli Sormin; Sarma Lumban Raja; Aida Fitria (Newinera Publisher, 2022)
The contentment of pregnant women throughout ANC and delivery may enhance the health of moms and infants. This research aims to determine what factors influence prenatal care for pregnant women in the Hinai Kiri Health Center Work Area, Secanggang District, Langkat Regency. This study employs a quantitative approach with a cross-sectional design, surveying 68 participants. This study employs a questionnaire. As a follow-up to the conclusion of the study, the research period is July to December 2021. This research included Univariate, Bivariate, and Multivariate analyses. The statistical tests used include the chi-square test and longitudinal regression. Knowledge (P-value = 0.003), Age (P-value = 0.002), Parity (P-value = 0.000), Husband's Support (P-value = 0.000), and Distance to Health Place (P-value = 0.004) were significant in a logistic regression analysis. Variables affecting the Antenatal Care Examination of Pregnant Women include knowledge, husband's support, age, and parity. This research concludes that there is a strong relationship between Knowledge, Husband's Support, and Parity and Antenatal Care Examinations for Pregnant Women in the Work Area of the Hinai Kiri Health Center in Secanggang District, Langkat Regency. Midwives on duty at the Hinai Kiri Health Center are expected to receive recommendations to improve counseling and counseling about the importance of routine pregnancy checks and to encourage pregnant women to be more routinely check their pregnancy at least four times during pregnancy so that the mother's health condition and the fetus are awake.